한국인 전반적 급진성 치주염 환자에서 IL-10 promoter 유전자 다변성에 관한 연구 - 류지선; 김옥수; Ryn, Ji-Sun; Kim, Ok-Su (Journal of Korean Academy of Periodontology, 2007)
Genetic polymorphisms associated with aggressive periodontitis have previously been reported. Interleukin-10 is an immunoregulatory cytokine that plays a role in the pathogenesis of periodontitis. Individual capacity for IL-10 production appears to be under genetic influence, The aim of present investigation was to explore possible genetic association of IL-10 gene promoter polymorphisms with generalized aggressive periodontitis. The study population consisted of 37 generalized aggressive periodontitis patients from the Department of Periodontology, Chonnam National University Hospital and 27 control subjects, all the subjects were non-smokers, Genomic DNA was obtained from buccal swab. The IL-10promoter -597, -824, -1082 positions were genotyped by amplifying the polymorphic regions using polymerase chain reaction (PCR) , followed by restriction enzyme digestion and gel electrophoresis. IL-10-597 C (allele 1) to A (allele 2) and IL-10-824 C (allele 1) to T (allele 2) and IL-10-1082 G (allele 1) to A (allele 2) polymorphisms were examined. The results were as follows. 1. In patients, the distribution of genotypes C/C, C/A and NA at Il-10-597 was determined to be 13.5%, 37.8% and 48.7%, respectively and the distribution of genotypes at IL-10-824 was the same as that of IL-10-597. The distribution of genotypes G/G, G/A and NA at IL-10-1082 was found to be 2.7%, 16.2% and 81. 4%, respectively. No statistical difference in genotype distribution was found between the patient and control groups. 2. Allele 2 carriage rate at the three position of the IL-10 promoter region was higher in the control group than the patient group. 3. Allele 2 frequencies at IL-10-597 and -824 positions were higher in female group than male group and its difference was statistically significant(p<0.05). No significant difference in genotype distribution between the control and patient groups. Allele frequency between control and patient groups was not significantly different although allele 2 frequency at the three positions in the IL-10 promoter region appeared to be higher in control group. In conclusion, no clear association between IL-10 gene promoter polymorphisms and generalized aggressive periodontitis in Korean was observed.